Influencing Factors Analysis of Local Environmental Regulation Implementation Behaviors in China: Theoretical Analysis and Empirical Test - Feng Pan; Lin Wang (Discrete Dynamics in Nature and Society)
It is a necessary means and a powerful point to promote the construction of ecological civilization by in-depth investigation of the implementation behaviors of local environmental regulation and effective identification their influencing factors. Using dynamic game method, the interaction between local government and pollution discharging enterprises is studied in the process of environmental regulation implementation, implementation behaviors and their influencing factors are analyzed, and empirically tested by Structural Equation Model. The results show that increasing marginal inspection budget and reducing marginal inspection cost can improve the inspection probability of local government; reducing the influence coefficient of enterprise profit on local government utility, increasing the weight coefficient of environmental indicators in the performance appraisal system, and increasing the administrative penalty rate, can improve the probability of levy and penalty on pollution discharging enterprises. Reducing the emission standard of pollution can increase the penalty probability; increasing pollution discharge fee rate will reduce the penalty probability on pollution discharging enterprises, while increasing the fine rate for excessive pollution will reduce the levy probability imposed on enterprises by local governments. Empirical test verifies the above theoretical analysis results. Based on the above research conclusions, it is necessary to revise incentive mechanism and restrain behavior orientation of local governments, gradually increase the environmental inspection budget, reduce the environmental inspection cost, increase rewards and punishments of environmental protection activities, reduce the influence of enterprise profit on local government utility, and scientifically formulate environmental protection standards.